1998
DOI: 10.1001/archsurg.133.12.1343
|View full text |Cite
|
Sign up to set email alerts
|

Third-Generation Cephalosporins and Vancomycin as Risk Factors for Postoperative Vancomycin-Resistant Enterococcus Infection

Abstract: To examine use of third-generation cephalosporins (3GCs) alone and in association with vancomycin hydrochloride as a risk factor for vancomycinresistant enterococcus (VRE) infection in surgical patients. Design: Case-control retrospective study analyzing antibiotic use in the 30 days preceding culture of VRE or vancomycin-sensitive enterococcus from an infected site. Setting: A large tertiary care teaching hospital. Patients: Surgical inpatients with VRE infections between September3,1993,andJanuary29,1997,wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 25 publications
1
28
1
2
Order By: Relevance
“…High rates of vancomycin or third-generation cephalosporin use have been reported to be associated with increased prevalence of VRE in hospitals [1,2,9,33,34]. The risk of VRE colonisation varies during exposure to different ␤-lactam antimicrobials, with higher tendency to promote colonisation in cefotetan, ceftriaxone or ceftazidime [7,12,33]. Our study also confirmed that consumption of all fluoroquinolones (but not injectable ciprofloxacin alone) is positively correlated with an increased rate of VRE.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…High rates of vancomycin or third-generation cephalosporin use have been reported to be associated with increased prevalence of VRE in hospitals [1,2,9,33,34]. The risk of VRE colonisation varies during exposure to different ␤-lactam antimicrobials, with higher tendency to promote colonisation in cefotetan, ceftriaxone or ceftazidime [7,12,33]. Our study also confirmed that consumption of all fluoroquinolones (but not injectable ciprofloxacin alone) is positively correlated with an increased rate of VRE.…”
Section: Discussionsupporting
confidence: 80%
“…Among the resistant Grampositive pathogens, methicillin (oxacillin)-resistant Staphylococcus aureus (MRSA), vancomycin-intermediate or -resistant S. aureus (VISA or VRSA) and vancomycinresistant enterococci (VRE) are of great concern because of the importance of these organisms in causing various types of nosocomial infections [1][2][3][4][5]. Increases in the prevalence of these resistant pathogens in hospitals are frequently related to the high selective pressure of antibiotics, including extended-spectrum cephalosporins, fluoroquinolones and glycopeptides [1,3,[6][7][8][9][10][11][12][13][14]. Newer antimicrobial agents (oxazolidinones, daptomycin and streptogramins) with novel antimicrobial mechanisms have been developed to 0924-8579/$ -see front matter © 2005 Elsevier B.V. and the International Society of Chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention address vancomycin use in instances of penicillin allergy by suggesting its appropriateness only when patients have a serious or life-threatening allergy to ␤-lactam antibiotics. 11 Many studies have established prior vancomycin use as a risk factor for colonization and infection with vancomycin-resistant enterococci, [12][13][14][15][16][17] yet it continues to be our hospital's most commonly prescribed antimicrobial agent. Not only does the high level of reported penicillin allergy often lead to the prescribing of agents we are trying to control in order to manage increasing resistance at our medical center, but, in some instances, the prescribing of alternate antimicrobial agents puts pa-tients at risk for colonization/infection with resistant organisms and/or treatment failure due to suboptimal therapy.…”
Section: Commentmentioning
confidence: 99%
“…5 And not just vancomycin: although vancomycin exerts selective pressure for the development of VRE, cephalosporins and antianaerobic agents are playing an increasingly important role in promoting colonization and infection. 6,7 Inhibition of competing bacteria, particularly by antianaerobic antibiotics with extensive biliary excretion, apparently accounts for VRE overgrowth. 7 Infections are just the tip of the iceberg: for every person with a full-blown VRE infection, 10 more are colonized, silently carrying the organism without symptoms.…”
Section: Vancomycin-resistant Enterococci (Vre) On the Risementioning
confidence: 99%